PO30 Study on the effect of the drying process of mint (Mentha sp.) on the yield and composition of essential oil and its encapsulation in β-cyclodextrin - Bustos Coral, Sebastian; Ávila Murillo, Mónica Constanza; Castellanos Marquez, Nelson Jair (Revista Productos Naturales, 2025)
It has been demonstrated that the drying process of plant material enhances the extraction of essential oils due to the weakening of cellular structures. Various drying methods have been described, including sun/shade drying, oven drying, and lyophilization, among others [1;2]. The aim of this research was to study the effect of shade drying on the composition and acetylcholinesterase inhibitory activity of peppermint (Mentha sp.) essential oil, as well as to evaluate encapsulation protocols in a cyclic oligosaccharide.